Iridium Incorporation into MnO2 for an Enhanced Electrocatalytic Oxygen Evolution Reaction. Issue 8 (29th March 2023) - Kakati, Uddipana; Elzinga, Evert J.; Mansley, Zachary R.; Roe, Benjamin; Alimohammadi, Farbod; Schwenk, Gregory; Ning, Jinliang; Zhu, Yimei; Ji, Hai‐Feng; Sun, Jianwei; Strongin, Daniel R.
Abstract: We have investigated the structure and activity of electrocatalysts for the oxygen evolution reaction (OER) that had low loadings of Ir incorporated into the 2D layered MnO2, (birnessite, nominally δ‐MnO2 ) and the 3D MnO2 (pyrolusite, β‐MnO2 ). The Ir‐incorporated β‐MnO2 (Ir/β‐MnO2 ) electrocatalysts were prepared for the first time via a thermally induced phase transition of δ‐MnO2 containing 16–22 wt% Ir. This phase transition of δ‐MnO2 to β‐MnO2 was facilitated by the presence of Ir in the structure, as both Ir in IrO2 and Mn in β‐MnO2 could adopt a thermodynamically favored rutile structure. Extended X‐ray absorption fine structure (EXAFS) of Ir/β‐MnO2 showed that the catalyst consisted of Ir substituted into the crystalline β‐MnO2 lattice. 22 wt% Ir/β‐MnO2 (60 μ g Ir cm geo - 2 μ g_Ir cm_geo^ - 2 ) exhibited an OER overpotential ( η η ) of 337 mV, lower than the η η for commercial IrO2 . This η η was constant for 6 h, at 10 mA cm geo - 2 cm_geo^ - 2 in 0.5 M H2 SO4 . EXAFS, high‐angle annular dark‐field scanning transmission electron microscopy (HAADF‐STEM) and X‐ray absorption near edge structure (XANES) showed that 22 wt% Ir/β‐MnO2 had a strained structure containing ∼41 % Mn 3+, an OER active species, along with a modified Ir bond covalency consisting of both Ir−O−Ir and Ir−O−Mn. Abstract : Ir/β‐MnO2 shows improved OER performance compared to Ir/δ‐MnO2 and IrO2 due to a strained lattice containing Ir−O−Mn structural motif with optimum bond strength, along with Mn 3+ an OER active species. (Spectator atoms are labelled as red O, olive Ir, and purple Mn. Blue arrows indicate atomic magnetic moments, spin up or spin down. The black line indicates the unit cell boundary).